2017
DOI: 10.1038/cddis.2017.71
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated CAV1 activates autophagy through an interaction with BECN1 under oxidative stress

Abstract: CAV1/Caveolin1, an integral membrane protein, is involved in caveolae function and cellular signaling pathways. Here, we report that CAV1 is a positive regulator of autophagy under oxidative stress and cerebral ischemic injury. Treatment with hydrogen peroxide enhanced autophagy flux and caused the localization of BECN1 to the mitochondria, whereas these changes were impaired in the absence of CAV1. Among many autophagy signals, only LC3 foci formation in response to hydrogen peroxide was abolished by CAV1 def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 52 publications
2
37
0
Order By: Relevance
“…The investigators concluded that autophagy activation following caveolin-1 knockdown might reflect an adaptive response to the marked increase in oxidative stress caused by decreased caveolin-1 protein expression in endothelial cells [80]. However, Nah J et al [81] revealed that the loss of caveolin-1 impairs autophagy and increases the infarct area following cerebral ischemia. Phosphorylated caveolin-1 at tyrosine-14 protects against cerebral ischemic damage by activating autophagy through its binding to the Beclin-1/VPS34 complex under conditions of oxidative stress [82].…”
Section: Crosstalk Between Caveolin and Autophagymentioning
confidence: 99%
“…The investigators concluded that autophagy activation following caveolin-1 knockdown might reflect an adaptive response to the marked increase in oxidative stress caused by decreased caveolin-1 protein expression in endothelial cells [80]. However, Nah J et al [81] revealed that the loss of caveolin-1 impairs autophagy and increases the infarct area following cerebral ischemia. Phosphorylated caveolin-1 at tyrosine-14 protects against cerebral ischemic damage by activating autophagy through its binding to the Beclin-1/VPS34 complex under conditions of oxidative stress [82].…”
Section: Crosstalk Between Caveolin and Autophagymentioning
confidence: 99%
“…Oxidative stress, characterized by increased ROS production, plays a key role in the regulation of cells survival [12]. Many drugs exert their negative effects on cancer cells are through increased the production of ROS [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in mouse embryonic fibroblasts, Cav-1 knockout promotes lysosomal function and increases LC3B-II expression via the disruption of lipid rafts to promote cell survival under starvation [49]. In contrast, Cav-1 can also function as a positive regulator of 17β-oestradiol mediated autophagy in BT474 human breast cancer cells [50] or autophagy-mediated claudin-5 degradation in oxygen-glucose deprivation-treated endothelial cells [54] and oxidative stress-activated autophagy [55], which involves the Cav-1/HMGB1 pathway [50], the autophagylysosome pathway and an interaction with Beclin-1. Moreover, some components of lipid rafts are reported to promote autophagy [56,57].…”
Section: Discussionmentioning
confidence: 99%